A Mathematical Model of Laser Drilling with Laser Absorption in the Plasma - Maturose Suchatawat (IOP Conference Series Materials Science and Engineering, 2021)
Abstract Despite being an accurate process with high processing speed, laser drilling suffers from several drawbacks including wall taper, recast layer and spatter. Hence, in order to improve the process efficiency and achieve the good hole quality, it is crucial to have a precise model which can be used as a tool to relate the process parameters to the process output. In this paper, an analytical model of laser drilling is developed. The governing equations are established from the energy equations at the solid-liquid and liquid-vapor interfaces. Absorption of laser energy in the plasma and an additional energy generated from the exothermic reaction are also included in the model. Aiming at simplifying the model, a constant value of the plasma absorption coefficient of the laser beam is employed. Validation of the model is done by comparing with the available experimental data. It is concluded that the recommended value of the plasma absorption coefficient for low carbon steel drilling is 0.2.
Keywords: Laser Material Processing Techniques; Laser-induced spectroscopy and plasma; Advanced Surface Polishing Techniques